Fans’ identification with teams: A field study of Israeli soccer fans - Cohen, Aaron (Cogent social sciences, 2017)
The goal of this study was to examine variables related to the identification of fans with their soccer team. Spectator motivations and psychological variables were examined in addition to control variables. The sample consisted of 350 soccer fans of a successful soccer team in the Israeli first division. The survey was conducted immediately before the team’s home game with the permission and support of the team’s owner, who requested (commissioned?) the study and was involved in the development of the research model. The results of a regression analysis show a strong positive relationship between commitment to the community and team identification. Of the motivation variables, eustress and aesthetics were found to have a positive and significant relationship with fans’ identification with the team. Level of happiness was also found to be related to team identification. The findings are discussed in terms of the need for more field studies such as the present study to compare the results with those of other previous studies, which were based on student samples.